Analisis Penerapan Akuntansi Di Dinas Perumahan Rakyat Dan Kawasan Permukiman Kota Metro - Siti Kholifah, Ulfi; Zanaria, Yulita; Nusantoro, Jawoto (Universitas Muhammadiyah Metro, 2024)
This research aims to determine the suitability of the application of accounting in the Metro City Public Housing and Residential Area Service. The type of research used is a qualitative descriptive method. The instruments used in this research are interviews and observations. Data analysis was carried out using the Miles and Huberman model. The research results show that the application of accounting in the Metro City Public Housing and Residential Area Service is not in accordance with Generally Applicable Accounting Principles. The accounting process carried out by the Metro City Perkim Service starts with all cash disbursement and cash receipt transactions which are recorded first in the General Cash Book (BKU). Document all transactions that occur and then journalize them. Transactions that cause cash disbursements are recorded in the cash disbursement journal and vice versa. It's just that the Department does not print out the journaling process and only makes it according to a computerized system.